The classic sci-fi ultimate collection - Universal-International (Firm); Universal Studios Home Entertainment (Firm) (Universal City, Calif. : Universal Studios Home Entertainment, 2008)
Get ready for the adventure of a lifetime with 10 fascinating films. Featuring amazing, groundbreaking special effects, these captivating and shocking classics from the golden age of Hollywood set the standard for all sci-fi to come.
Vol. 1 [Disc one] [1] Tarantula (1955; 81 min.) -- [2] The Mole people (1956; 78 min.) -- [Disc two] [1] The incredible shrinking man (1957; 81 min.) -- [2] The Monolith monsters (1957; 78 min.) -- [Disc three] [1] Monster on the campus (1958; 77 min.) -- Vol. 2 [Disc one] [1] Dr. Cyclops (1940; 78 min.) -- [2] Cult of the cobra (1955; 80 min.) -- [Disc two] [1] The land unknown (1957; 79 min.) -- [2] The deadly mantis (1957; 79 min.) -- [Disc three] [1] The leech woman (1959; 78 min.).
Universal Studios Home Entertainment: 61104061.
Includes original theatrical trailers.
Originally produced by Universal-International as motion pictures in 1940-1959.
DVD, full frame (1.33:1) and widescreen (1.78:1), Dolby digital mono.
Closed-captioned; optional French subtitles.
Keywords: Feature films; Science fiction films; Horror films; Fiction films; Films for the hearing impaired; Feature films; Science fiction films; Horror films; Fiction films; Video recordings for the hearing impaired